Peranan Atoin Amaf Dalam Tradisi Adat Tatam Ut di Masyarakat Kecamatan Amatun Selatan Kabupaten Timor Tengah Selatan - Febe Priskila Tefa; Hiwa Wonda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Customary traditions are an important part of the cultural identity of the community that is passed down from generation to generation. This study aims to analyze the role of Atoin Amaf in the Tatam Ut tradition, a Timorese tradition, especially in the South Amanatun District, where sisters bring offerings of corn-based foods to their brother as a symbol of respect and family ties. The study used a descriptive qualitative method in data collection techniques through interviews, participatory observation, and literature studies. The result show that Atoin Amaf plays an important role as a traditional leader, social mediator, and guardian of cultural values in the implementation of the Tatam Ut tradition. He functions to regulate ceremonial precedures, uphold customary norms, and instill the values of respect, compassion, and solidarity among family members.In addition, modern social changes demand efforts to revitalize the role of Atoim Amaf so that this tradition remains relevant in the current era. In conclusion, Atoin Amaf is a key figure in maintaining the continuity of the Tatam Ut tradition as a cultural heritage that reflects the harmony, respect, and brotherhood of the Timorese people in the South Amanatun District.